2003
DOI: 10.1029/2003jb002653
|View full text |Cite
|
Sign up to set email alerts
|

Current tectonics of northern Cascadia from a decade of GPS measurements

Abstract: [1] Global Positioning System (GPS) measurements to study regional deformation were initiated in northern Cascadia in the late 1980s and early 1990s. On the basis of a decade of GPS data, we derive a crustal velocity field for NW Washington-SW British Columbia. The permanent and campaign GPS velocities are defined with respect to North America in the ITRF2000 reference frame. Velocity uncertainties are estimated using a model of time series noise spectra. This new velocity field is the basis for interpretation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
75
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(79 citation statements)
references
References 60 publications
(118 reference statements)
3
75
0
1
Order By: Relevance
“…Analyses of GPS data from these sites have confirmed that long-term elastic deformation occurs along the northern Cascadia Margin due to the locking of converging plates across a portion of the subduction interface between the Juan de Fuca plate and the overlying North America (NA) plate (cf. Mazzotti et al, 2003). The motion vectors shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Analyses of GPS data from these sites have confirmed that long-term elastic deformation occurs along the northern Cascadia Margin due to the locking of converging plates across a portion of the subduction interface between the Juan de Fuca plate and the overlying North America (NA) plate (cf. Mazzotti et al, 2003). The motion vectors shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Deep afterslip has been observed for several large subduction events (Hutton et al, 2001;Melbourne et al, 2002;Zweck et al, 2002). It has been shown in some cases to coincide with the transition zone between the LFZ and the zone creeping at the long-term slip rate (Dragert et al, 1994;Mazzotti et al, 2003;Chlieh et al, 2004b). In most cases, even though some component of large-scale viscous relaxation might be present, deep afterslip seems to evolve as predicted by ratestrengthening frictional sliding (Montesi, 2004;Perfettini et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…Data time spans vary from 1992 to 2008, with an average time series length of 5-6 years. Details of the regional network processing are given in Mazzotti et al [2003b] and Leonard et al [2007]. The various networks are combined, aligned to the International Terrestrial Reference Frame ITRF2000, and referenced to stable North America using the North America/ITRF2000 rigid rotation [cf.…”
Section: Gps Data and Strain Ratesmentioning
confidence: 99%
“…It comprises 179 horizontal velocity vectors derived from 89 continuous and 90 campaign GPS stations throughout Alberta, British Columbia, and northern Washington [Henton et al, 2006;Leonard et al, 2007;Mazzotti et al, 2003aMazzotti et al, , 2003b] (see auxiliary material). Data time spans vary from 1992 to 2008, with an average time series length of 5-6 years.…”
Section: Gps Data and Strain Ratesmentioning
confidence: 99%
See 1 more Smart Citation